WOMEN'S HEALTH CARE IN THE FAMILY HEALTH PROGRAM: PRE-PROFESSIONAL EXPERIENCE WITH AN EMPHASIS ON CERVICAL CANCER PREVENTION - Rosane Seeger da Silva; Seomara Espindola Weissheimer; Sabrina Hardt Torri; Débora Einloft; Maria Rozane Campanholo Coelho; Jodete Medianeira Niederauer Brasil; Roselaine Pinheiro Antunes (Artefactum - revista de estudos interdisciplinares, 2026)
This study, conducted as a course completion project, aims to highlight the importance of administrative and care-related nursing activities within Family Health Program (PSF) units in a municipality in the interior of Rio Grande do Sul. It seeks to develop nursing competencies regarding women's health—specifically concerning cervical cancer—and to address health education issues by devising health promotion strategies tailored to the local context of this population. The methodology involved carrying out practical activities at a Basic Health Unit (UBS) between August 15, 2023, and November 23, 2023, totaling 405 hours. To conduct the study, the researchers systematized topics related to nursing practice during gynecological consultations, focusing on the collection of cervical cytology samples. The study was developed through pre-scheduled monthly meetings among the nursing students. This experience report is organized into thematic categories derived from the students' practical experiences and the key actions performed within the municipal Primary Health Care (PHC) system. These categories are: "actions performed during nursing consultations for cervical cytology collection" and "challenges in nursing care regarding cervical cytology collection." Thus, it is worth noting that the study successfully identified the barriers hindering women's adherence to screening and the challenges nurses face in their daily practice regarding the Pap smear exam.